2015
DOI: 10.11648/j.aff.20150403.20
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Allanblackia floribunda Seeds: The Effect of Soak Duration in Fluridone on Germination and Seedling Growth

Abstract: Abstract:Allanblackia seeds contain about 72% white fat (mostly of oleic and stearic acid), with high medicinal and industrial value, but the plant has not been domesticated, so seeds are only gotten from the wild. The demand for seeds of the wild Allanblackia floribunda exceeds supply and efforts to domesticate the plant to increase seed availability have been unsuccessful due to long seed dormancy periods. Soaking scarified seeds from immature fruits in water or fluridone shortened dormancy to less than 3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Ofori et al (2011) reported that seeds of A. parviflora were dormant, taking 7 months after sowing for germination to begin, and that removal of the seed coat promoted germination. Seeds of A. floribunda also are dormant (Ileleji et al, 2015). However, the seeds of S. globulifera were reported by Côme (1986, 1988) to be nondormant.…”
Section: Physiological Dormancy In Garcinia (Clusiaceae)mentioning
confidence: 97%
“…Ofori et al (2011) reported that seeds of A. parviflora were dormant, taking 7 months after sowing for germination to begin, and that removal of the seed coat promoted germination. Seeds of A. floribunda also are dormant (Ileleji et al, 2015). However, the seeds of S. globulifera were reported by Côme (1986, 1988) to be nondormant.…”
Section: Physiological Dormancy In Garcinia (Clusiaceae)mentioning
confidence: 97%